THE SYSTEM OF MOTIVES OF EDUCATIONAL ACTIVITY AS A PROGNOSTIC SYSTEM SUCCESS FACTORS IN LEARNING: VIEW THROUGH THE PRISM OF UNIFICATIONNOW APPROACH - A. Egorova; S. Bobryshov (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes modern views on classification structures and substantiation of features of educational motivation based on the unified approach. In a comparative way, the content, structural, and functional parameters of the motives of educational activity considered by various scientists are revealed. Based on the identification of the essential characteristics of internal and external educational motivation, its relationship with groups of motives is established, which are defined as the motives inherent in the educational activity itself, and the motives associated with the result of teaching. It is proved, that in the conditions of the educational process, the motives of educational activity act as a single essential-semantic, structural, determinational and functional system, and its detailed characteristics are given. The strengths and weaknesses of individual groups of educational motives are systematized, and the factors that determine their effectiveness and effectiveness in ensuring the success of training are shown.